Functional value

Algebra Level 4

f ( n ) = a n + b n + c n , f ( 1 ) = 1 , f ( 2 ) = 2 , f ( 3 ) = 3 f(n)=a^n+b^n+c^n, f(1)=1, f(2)=2, f(3)=3 , then, f ( 5 ) = f(5)= ?


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Sakib Hrid
Jan 29, 2015

f ( n ) = a n + b n + c n f(n)=a^n+b^n+c^n

So,

f ( 1 ) = a + b + c = 1 f(1)=a+b+c=1 .......(1)

f ( 2 ) = a 2 + b 2 + c 2 = 2 f(2)=a^2+b^2+c^2=2 ......(2)

f ( 3 ) = a 3 + b 3 + c 3 = 3 f(3)=a^3+b^3+c^3=3 .......(3)

We know,

a b + b c + c a = ( a + b + c ) 2 ( a 2 + b 2 + c 2 ) 2 ab+bc+ca=\dfrac{(a+b+c)^2-(a^2+b^2+c^2)}{2}

i.e. a b + b c + c a = ( 1 ) 2 2 2 ab+bc+ca=\dfrac{(1)^2-2}{2}

So,

a b + b c + c a = 1 2 ab+bc+ca=\dfrac{-1}{2} .......(4)

Again we know,

a 3 + b 3 + c 3 3 a b c = ( a + b + c ) ( a 2 + b 2 + c 2 ( a b + b c + c a ) ) a^3+b^3+c^3-3abc=(a+b+c)(a^2+b^2+c^2-(ab+bc+ca))

3 3 a b c = 2 + 1 2 3-3abc=2+\dfrac{1}{2}

3 a b c = 1 2 -3abc=\dfrac{-1}{2}

a b c = 1 6 abc=\dfrac{1}{6}

36 a 2 b 2 c 2 = 1 36a^2b^2c^2=1 ............(5)

From (2)×(3) we get,

( a 2 + b 2 + c 2 ) ( a 3 + b 3 + c 3 ) = 6 (a^2+b^2+c^2)(a^3+b^3+c^3)=6

a 5 + b 5 + c 5 + ( a 2 b 3 + a 2 c 3 + b 2 a 3 + b 2 c 3 + c 2 a 3 + c 2 b 3 ) = 6 a^5+b^5+c^5+(a^2b^3+a^2c^3+b^2a^3+b^2c^3+c^2a^3+c^2b^3)=6

a 5 + b 5 + c 5 + ( b a 2 b 2 + c a 2 c 2 + a a 2 b 2 + c b 2 c 2 + a c 2 a 2 + b b 2 c 2 ) = 6 a^5+b^5+c^5+(ba^2b^2+ca^2c^2+aa^2b^2+cb^2c^2+ac^2a^2+bb^2c^2)=6

From (6)

a 2 b 2 = 1 / 36 c 2 a^2b^2=1/36c^2

b 2 c 2 = 1 / 36 a 2 b^2c^2=1/36a^2

c 2 a 2 = 1 / 36 b 2 c^2a^2=1/36b^2

so,

a 5 + b 5 + c 5 + ( b / 36 c 2 + c / 36 b 2 + a / 36 c 2 + c / 36 a 2 + a / 36 b 2 + b / 36 a 2 ) = 6 a^5+b^5+c^5+(b/36c^2+c/36b^2+a/36c^2+c/36a^2+a/36b^2+b/36a^2)=6

a 5 + b 5 + c 5 + ( a + b ) / 36 c 2 + ( b + c ) / 36 a 2 + ( c + a ) / 36 b 2 = 6 a^5+b^5+c^5+{(a+b)/36c^2+(b+c)/36a^2+(c+a)/36b^2}=6

a 5 + b 5 + c 5 + ( 1 c ) / 36 c 2 + ( 1 a ) / 36 a 2 + ( 1 b ) / 36 b 2 = 6 a^5+b^5+c^5+{(1-c)/36c^2+(1-a)/36a^2+(1-b)/36b^2}=6

a 5 + b 5 + c 5 + a 2 b 2 ( 1 c ) + b 2 c 2 ( 1 a ) + c 2 a 2 ( 1 b ) / 36 a 2 b 2 c 2 = 6 a^5+b^5+c^5+{a^2b^2(1-c)+b^2c^2(1-a)+c^2a^2(1-b)}/36a^2b^2c^2=6

a 5 + b 5 + c 5 + a 2 b 2 + b 2 c 2 + c 2 a 2 a b c ( a b + b c + c a ) = 6 a^5+b^5+c^5+{a^2b^2+b^2c^2+c^2a^2-abc(ab+bc+ca)}=6

a 5 + b 5 + c 5 + a 2 b 2 + b 2 c 2 + c 2 a 2 + 1 / 12 = 6 a^5+b^5+c^5+{a^2b^2+b^2c^2+c^2a^2+1/12}=6 ........(6)

Now, squaring (4) we get,

( a b + b c + c a ) 2 = 1 / 4 (ab+bc+ca)^2=1/4

a 2 b 2 + b 2 c 2 + c 2 a 2 + 2 a b c ( a + b + c ) = 1 / 4 a^2b^2+b^2c^2+c^2a^2+2abc(a+b+c)=1/4

a 2 b 2 + b 2 c 2 + c 2 a 2 + 2 1 / 6 1 = 1 / 4 a^2b^2+b^2c^2+c^2a^2+2*1/6*1=1/4

a 2 b 2 + b 2 c 2 + c 2 a 2 = 1 / 12 a^2b^2+b^2c^2+c^2a^2=-1/12

From (6) we get,

a 5 + b 5 + c 5 + ( 1 / 12 + 1 / 12 ) = 6 a^5+b^5+c^5+(-1/12+1/12)=6

a 5 + b 5 + c 5 = 6 a^5+b^5+c^5=6

f ( 5 ) = a 5 + b 5 + c 5 = 6 f(5)=a^5+b^5+c^5=6

Using Newton's Sum is a way short method !!!!

Akshat Sharda - 5 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...